2020
DOI: 10.1021/acs.jmedchem.0c01883
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Retinoid X Receptor Binding Assay Based on Fluorescence Change of the Antagonist NEt-C343

Abstract: Retinoid X receptor (RXR) modulators (rexinoids) are considered to have therapeutic potential for multiple diseases, such as Alzheimer’s disease and Parkinson’s disease. To overcome various disadvantages of prior screening methods, we previously developed an RXR binding assay using a fluorescent RXR ligand, CU-6PMN (4). However, this ligand binds not only at the ligand-binding domain (LBD) but also at the dimer–dimer interface of hRXRα. Here, we present a new fluorescent RXR antagonist 6-[N-ethyl-N-(5-isobutox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 40 publications
(105 reference statements)
0
12
0
Order By: Relevance
“…Most reported RXR ligands bind in modes in which the carboxy group enters the LBP, whereas our X-ray cocrystal analysis indicated that the carboxy group of 4a is directed outside the hRXRα-LBP, and instead, the alkoxy chain is located inside the LBP . In addition, an AutoDock docking simulation of our previously reported fluorescent RXR antagonist NEt-C343 ( 5 ) suggested that 5 has a similar binding mode to 4a , i.e., that the fluorophore coumarin 343 (C343), not the carboxy group, enters the LBP …”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Most reported RXR ligands bind in modes in which the carboxy group enters the LBP, whereas our X-ray cocrystal analysis indicated that the carboxy group of 4a is directed outside the hRXRα-LBP, and instead, the alkoxy chain is located inside the LBP . In addition, an AutoDock docking simulation of our previously reported fluorescent RXR antagonist NEt-C343 ( 5 ) suggested that 5 has a similar binding mode to 4a , i.e., that the fluorophore coumarin 343 (C343), not the carboxy group, enters the LBP …”
mentioning
confidence: 69%
“…18 In addition, an AutoDock docking simulation of our previously reported fluorescent RXR antagonist NEt-C343 (5) suggested that 5 has a similar binding mode to 4a, i.e., that the fluorophore coumarin 343 (C343), not the carboxy group, enters the LBP. 19 Consequently, we were interested to see whether the introduction of a fluorescent group at the end of the alkoxy chain of 4a would afford fluorescent RXR-antagonistic derivatives whose fluorophore would enter the LBP. Compounds that show changes in fluorescence properties in response to a change in the environment or a decrease in molecular motility are expected to be applicable for RXR ligand-binding assays.…”
mentioning
confidence: 99%
“…The nuclear retinoid X receptor (RXR) comprises a ligand-activated transcription factor family existing in three highly conserved isoforms (RXRα, NR2B1; RXRβ, NR2B2; and RXRγ, NR2B3). , The RXRs fulfill a central role in the nuclear receptor superfamily acting not only as universal heterodimer partners but also as homodimers regulating gene expression. Several fatty acids and vitamin A metabolites have been discovered as RXR agonists among which 9- cis retinoic acid ( 1 , Chart ) is the most potent ligand. As the only approved synthetic rexinoid, bexarotene ( 2 ) is used as second-line treatment in cancer; ,, however, its use has been associated with severe adverse effects. , Considerable preclinical evidence suggests a high therapeutic potential of RXR activation to counteract neurodegenerative diseases such as multiple sclerosis and Alzheimer’s disease. Despite recent progress in targeting RXRs, , new potent RXR agonists are needed to overcome the limitations of traditional rexinoids, such as exceptional lipophilicity, poor pharmacokinetics (PK), and pronounced toxicity, , to further probe and exploit the highly promising pharmacological potential of RXR modulation.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported methods to screen for modulators targeting retinoid X receptors (RXRs), which are multifunctional nuclear receptors. , Lifestyle-related diseases such as cancer and type 2 diabetes are thought to be associated with “metaflammation,” which is the result of metabolic imbalance in the body . Metabolic homeostasis is maintained by the function of nuclear receptors (NRs) .…”
mentioning
confidence: 99%
“…In RXR research, FQA is widely used in the analysis of interactions between RXRs and their ligands and in screening for natural or synthetic RXR modulators. ,, FQA evaluates the ligand-binding ability ( K d ) based on quenching of the fluorescence around 330 nm due to Trp282 and Trp305 in the RXR-ligand binding domain (LBD) . There are at least 17 reports that have discussed RXR-modulating activity in terms of K d evaluated by FQA. ,, However, as mentioned above, this may lead to erroneous conclusions.…”
mentioning
confidence: 99%